STRENGTHENING MARKETING PERFORMANCE STRATEGIES FOR CULINARY MSMES: THE MEDIATING ROLE OF PRODUCT INNOVATION IN MARKET KNOWLEDGE - Bord Nandre Aprila; Sarli Rahman; Eliza Sofian Putri; Pujiono Pujiono (Procuratio : Jurnal Ilmiah Manajemen, 2024)
This research aims to analyze the influence of Market Knowledge and Product Innovation on Marketing Performance in MSMEs in the culinary sector in Pekanbaru City. The research sample was selected using a purposive sampling method based on criteria relevant to the research objectives, with a total of 200 respondents. The analysis method used is path analysis with the help of SPSS version 21 and SmartPLS 3 software. The research results show that Market Knowledge has a significant influence on Product Innovation and Marketing Performance. However, Product Innovation does not show a significant influence on Marketing Performance. Apart from that, Market Knowledge also has a significant influence on Marketing Performance through the mediation of Product Innovation. Penelitian ini bertujuan untuk menganalisis pengaruh Market Knowledge dan Inovasi Produk terhadap Kinerja Pemasaran pada UMKM sektor kuliner di Kota Pekanbaru. Sampel penelitian dipilih menggunakan metode purposive sampling berdasarkan kriteria yang relevan dengan tujuan penelitian, dengan jumlah total 200 responden. Metode analisis yang digunakan adalah analisis jalur (path analysis) dengan bantuan perangkat lunak SPSS versi 21 dan SmartPLS 3. Hasil penelitian menunjukkan bahwa Market Knowledge memiliki pengaruh signifikan terhadap Inovasi Produk dan Kinerja Pemasaran. Namun, Inovasi Produk tidak menunjukkan pengaruh signifikan terhadap Kinerja Pemasaran. Selain itu, Market Knowledge juga memiliki pengaruh signifikan terhadap Kinerja Pemasaran melalui mediasi Inovasi Produk.